Bahasa dan Penemuan Hukum Analisis Makna pada Pasal-Pasal dalam KUHP - Frans Sayogie (Buletin Al-Turas, 2007)
This research aims at analysing the meaning of articles of PenalCode Book. The research findings state that some of the articles of Penal Code Book are re quired to be interpreted in order to gain the clear meaning.